Prognostic Value of Cytochrome C and Cytokines in Acute Viral Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Serum cytochrome c and cytokines were evaluated as prognostic predictors in 29 children (ages 9 mos to 9 yrs 11 mos) with viral acute encephalopathies and multiple organ failure at Fukushima Medical University School of Medicine, Japan.